2014
DOI: 10.1016/j.progpolymsci.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Specific control of cell–material interactions: Targeting cell receptors using ligand-functionalized polymer substrates

Abstract: Cells respond to their environment in complex and sometimes poorly understood ways. Protein, peptide and synthetic peptidomimetic ligands may all be used to stimulate cells via receptor signaling, using interactions that are often highly specific. Polymer substrates that present these ligands provide a promising way to control cell development, both for applications in biotechnology and for fundamental studies of cell biology. Here we review a large range of techniques that have been employed to create and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 383 publications
(572 reference statements)
0
43
0
1
Order By: Relevance
“…Conformational changes caused by a flexible and/or too long spacer can result in the shielding of the active site [10,36,44,66]. In a recent study, we showed that the bulky and more rigid polyproline sequence used in compound 3 leads to a reduction in packing density when self-assembled on gold, compared with the alkane-based ligand [43].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conformational changes caused by a flexible and/or too long spacer can result in the shielding of the active site [10,36,44,66]. In a recent study, we showed that the bulky and more rigid polyproline sequence used in compound 3 leads to a reduction in packing density when self-assembled on gold, compared with the alkane-based ligand [43].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, novel strategies were developed, based on the engineering of biomimetic matrices for controlled stimulation of cells in vitro, particularly in key biomedical applications such as stimulation of immune cells, controlling pluripotency and regulating cell migration [9,10]. The use of such surfaces enabled testing the effects of ECM ligands diversity, as well as the effects of integrin receptor occupancy and clustering [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [7][8][9][10][11][12] However, investigators have only recently begun to evaluate the potential importance of physical cues on stem cell differentiation, such as cell shape, cell culture polymeric biomaterial stiffness, 13 mechanical force (e.g., shear stress imposed by culture media and cyclic stretching of biomaterials), 14 and external force (e.g., electrical forces, magnetic forces, and light signals) (Fig. 1).…”
Section: Medicinementioning
confidence: 99%
“…For example, extensive work has been done tuning material stiffness [5] and the nano/microscale morphology, [6] and these properties have both been shown to significantly affect cell differentiation and proliferation. [7] While tuning an individual biochemical or physical cue can enable study of its effect in isolation and enhance material performance, [8] multiple biomimetic cues often have a synergistic effect, such that the overall benefit is greater than the combined individual benefits. [7b,9] This makes it important to include and optimize as many aspects of the ECM as synthetically possible in order to achieve the greatest therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%